Managing the customer risk experience in business-to-business purchasing – How can cyber security influence customer journey - Kähäri, Eemil (My University, 2024)
In the marketing of business-to-business (B2B) technology providers, there is a constant reduction in the budget allocated for customer experience (CX). Studies have shown that B2B providers need to excel in customer experience management (CXM). Providers need to understand the origin of CX to manage it effectively. There has been a demonstrated connection between purchasing behaviour and customer experience. Customer experience occurs during the customer journey (CJ). One factor impacting the customer journey is the necessity for cyber security. Cyber security is to be integrated into B2B machine supply to improve customer experience at the customer journey. This needs customer risk experience management. Recent studies on B2B marketing management have neglected this combination of the customer’s risk experience, such as a cyber security risk experience in industrial purchasing and B2B customer management. The purpose of this thesis is to clarify how to manage the customer’s risk experience related to cyber security in B2B purchasing. This research utilized a qualitative research method and gathered data through semi-structured individual interviews with sales management of B2B providers. Results obtained showed a connection of how providers want to understand their customers and customer experiences better but do not always know how to manage their business in real life as needed. Cyber security is offered in the way assumed by theory during purchasing. Thus, the provider company must be able to influence its customers' purchasing during the customer journey. The customer company and their representative can always be different. Thus, the sales must be sufficiently adaptable to this. This adaptability is achieved best through customer trust. For trust to be possible, the provider must be as open as possible towards the customer in its selling. To manage customer’s risk experience related to cyber security in B2B purchasing the provider needs to facilitate openness and trustworthiness. The results confirmed existing research in many ways, particularly in the context of B2B provider companies. The existing theory was further supplemented with a better understanding of the importance of openness. However, there is still little research into the impact of customer experiences on purchasing. The obtained results can be theoretically linked to the development of B2B marketing management, highlighting the need to further manage customer experiences by understanding emotions and managing customer risk experiences. This understanding can be applied in further studies related to this topic.

Yritysten välisen liiketoiminnan (B2B) markkinoinnissa budjettia, joka on kohdennettu asiakaskokemukseen (CX), vähennetään jatkuvasti. Tutkimukset ovat osoittaneet, että B2B- toimittajien on oltava erinomaisia asiakaskokemuksen hallinnassa (CXM). Toimittajien on ymmärrettävä asiakaskokemuksen alkuperä johtaakseen sitä tehokkaasti. On osoitettu yhteys ostokäyttäytymisen ja asiakkaiden tunteiden välillä, mikä tapahtuu asiakaspolun (CJ) aikana. Yksi asiakaspolkuun vaikuttava tekijä on kyberturvallisuuden tarve. Kyberturvallisuus on integroitu B2B-koneiden toimitukseen parantamaan asiakaskokemusta asiakaspolulla. Tämä vaatii asiakasriskikokemuksen johtamista. Viimeaikaiset tutkimukset B2B-markkinointitutkimuksessa ovat jättäneet huomiotta tämän yhdistelmän; Asiakkaan riskikokemus, kuten kyberturvallisuusriski teollisissa hankinnoissa ja B2B-asiakashallinnassa. Tämän opinnäytetyön tarkoituksena on selkeyttää sitä, miten johtaa asiakkaan riskikokemusta, joka liittyy kyberturvallisuuteen B2B-hankinnoissa. Tässä tutkimuksessa käytettiin kvalitatiivista tutkimusmenetelmää ja kerättiin tarvittava aineisto puolistrukturoiduilla yksilöhaastatteluilla B2B-toimittajien myynnin johdon kanssa. Saatujen tulosten mukaan toimittajat haluavat ymmärtää asiakkaitaan ja heidän kokemuksiaan paremmin, mutta eivät aina tiedä, miten johtaa liiketoimintaansa käytännössä tarvittavalla tavalla. Tietoturvaa tarjotaan teoriassa oletetulla tavalla ja sitä tarjotaan asiakkaille aktiivisesti. Toimittajayrityksen on pystyttävä vaikuttamaan asiakkaidensa ostoihin asiakaspolun aikana. Asiakasyritys ja heidän edustajansa voivat aina olla erilaisia. Siksi myynnin on oltava riittävän mukautuvaa. Tämä mukautuvuus saavutetaan parhaiten asiakasluottamuksen kautta. Luottamuksen mahdollistamiseksi toimittajan on oltava mahdollisimman avoin asiakasta kohtaan myyntitilanteessa. Tulokset vahvistivat olemassa olevaa tieteellistä tutkimusta, erityisesti B2B- konetoimittajayritysten kontekstissa. Jo olemassa oleva teoria täydentyi paremmalla ymmärryksellä avoimuuden tärkeydestä. Tutkimusta asiakaskokemusten vaikutuksesta ostoihin on kuitenkin edelleen vähän. Saadut tulokset voidaan teoreettisesti liittää B2B-markkinoinnin johtamisen kehittämiseen, korostaen tarvetta johtaa asiakaskokemuksia paremmin ymmärtämällä tunteita ja johtamalla riskiasiakaskokemuksia. Tätä saatua ymmärrystä voidaan soveltaa jatkotutkimuksissa liittyen samaan kontekstiin.
Keywords: Business-to-business, CXM, customer risk experience management